Small cell conversion complicated with hypertrophic pulmonary osteoarthropathy after targeted therapy for advanced EGFR-mutated lung adenocarcinoma: A case report - Sijia Zhang; Leichong Chen; Kuikui Zhu; Rui Meng (Wolters Kluwer Medknow Publications, 2024)
In recent years, with the opening of the era of precision therapy, the treatment of patients with positive driver genes is a hot issue in global research. EGFR is the most common driver gene in NSCLC, with a positivity rate of 17%. Although targeted drugs for EGFR mutations can benefit this population with efficacy, target therapy resistance inevitably occurs. The presented case suggests that a patient with advanced lung adenocarcinoma with EGFR mutation who developed pathological-type conversion of small cell lung cancer complicated with the development of hypertropic pulmonary osteoarthropathy (HPOA) after 6 months of targeted therapy. This case demonstrates that early diagnosis of HPOA can predict the occurrence of target resistance and pathologic conversion in patients with positive driver genes, providing new clues for the clinical management of lung cancer.